Job satisfaction of adjunct community college faculty in the Midwest post-COVID-19 - Kasuboski, Stephanie Sanbe (My University, 2025)
COVID-19 was officially declared a pandemic by the World Health Organization on March 11, 2020, and it quickly affected everyone’s life as new protocols were established in all areas. The effects of the pandemic were long lasting, and many areas have not yet fully recovered. Community colleges were not immune to the challenges faced during the pandemic, and they continue to face them in a postpandemic environment. Course offerings, student enrollment, and course modalities changed seemingly overnight. Changes to students’ expectations and needs forced academic institutions to reexamine many aspects of their operations to meet the new normal created by the pandemic. To meet budgetary constraints, there has been a greater reliance on adjunct faculty at community colleges. Looking at job satisfaction and the factors that affect job satisfaction is vital to ensure there is a robust pool of qualified adjunct faculty to meet the needs of community colleges. This study was a quantitative research study with descriptive, comparative, and correlation and regression analyses. Using Maslow’s hierarchy of needs as the theoretical framework and Herzberg’s two-factor theory of motivation and hygiene as the conceptual framework, adjunct faculty teaching at nine community colleges, accredited by the Higher Learning Commission, in the Midwest, during the Spring 2024 semester were surveyed to determine their levels of job satisfaction and the factors that affect job satisfaction. The results were compared to the trends of job satisfaction found in a previous 2010 study. The results of this study show that 72.4% of adjunct faculty are satisfied with their jobs. They are most satisfied with the autonomy and independence and freedom to design course content that is afforded by their job. In addition, adjunct faculty are most satisfied with the competency of their colleagues and departmental leadership. Adjunct faculty are least satisfied with their prospects for career advancement, institutional support of travel for professional development, and benefits. There has been a slight decrease in the overall satisfaction of adjunct faculty from 2010 (M = 3.0) to 2024 (M = 2.9). However, the factors affecting job satisfaction have remained consistent across the two studies. The results of this study offer a comprehensive view of adjunct faculty, and an insight into what can be done to improve the teaching experience of adjunct faculty.
Keywords: Adjunct faculty; Community college; Job satisfaction; Herzberg; Maslow; Midwest